Modeling Marine Geoid in the China Seas and Its Adjacent Ocean Based on Satellite Altimeter-Derived Gravity Anomaly Model - Huiying Zhang; Xin Liu; Zhen Li; Xiaotao Chang; Heping Sun; Hui Li; Jinyun Guo (IEEE Access)
The marine geoid can be determined through the utilization of the marine gravity anomaly model. The accuracy of retrieving marine gravity anomaly model with altimetry data has been improved due to the abundance and high quality of available altimetry data. The SDUST2022 GRA marine gravity anomaly model is the global marine gravity anomaly model constructed by integrating multi-source altimeter satellites, including ICEsat-2 laser altimeter satellite for the first time. The model optimizes the deflection of the vertical accuracy imbalance. The Stokes formula is employed in this study to construct the geoid model, while the two-dimensional fast Fourier transform convolution in planar coordinate is utilized to enhance computational efficiency. Additionally, the remove-computer-restore method is applied during the calculation process. Firstly, the accuracy of the algorithm is verified using the 2190-degree XGM2019e_2159 gravity field model and the 2159-degree EGM2008 gravity field model. Subsequently, the XGM2019e_2159 is removed from the SDUST2022 GRA marine gravity anomaly model, and the residual geoid height is computed utilizing the Stokes formula. Then, the geoid height of the corresponding reference field is restored. Finally, a geoid model for China Sea and its adjacent ocean is constructed. The results showed that the geoid of the China Sea and its adjacent ocean gradually increases from west to east, and the longwave and shortwave characteristics of the seafloor can be clearly seen. The reliability of the model established in this paper was verified by the least-squares collocation method, and the geoid model calculated by the two methods had a good consistency. The mean sea surface model was introduced to calculate the mean dynamic topography. According to the mean dynamic topography, the Kuroshio Extension and the mesoscale eddy phenomenon caused by the instability of background current could be clearly seen. Compared with the mean dynamic topography of DTU22MDT, the difference between the two mean dynamic topography was basically within the range of centimeters. This showed that the mean dynamic topography of the China Sea and its adjacent ocean calculated in this paper was reliable, that is, the geoid of the China Sea and its adjacent ocean constructed in this paper was reliable.